A Comparative Study of Antibacterial Activity of CuO/Ag and ZnO/Ag Nanocomposites - R. B. Asamoah; E. Annan; B. Mensah; P. Nbelayim; V. Apalangya; B. Onwona-Agyeman; A. Yaya (Advances in Materials Science and Engineering)
The synergistic effects of transition metal based nanocomposites are known to possess enhanced antibacterial activities. However, in-depth analysis of the relative antibacterial performance of some of the prominent nanocomposites remains unavailable. This study compares the antibacterial activity of two separate nanocomposites, which are copper oxide with silver (CuO/Ag) and zinc oxide with silver (ZnO/Ag). The individual CuO/Ag and ZnO/Ag nanocomposites were synthesised by a mixed wet-chemical method. The resulting particles were analysed by XRD, XRF, TEM, UV-Vis spectrophotometer, BET, and FTIR. The antibacterial activity of the nanoparticles were tested on Gram-negative and Gram-positive bacteria, Escherichia coli (ATCC25922) and Staphylococcus aureus (ATCC25923), respectively, using the Kirby–Bauer disc diffusion and the microdilution methods. The Kirby–Bauer disc diffusion test results had the same minimum inhibition concentration (MIC) value for both CuO/Ag and ZnO/Ag against E. coli and S. aureus, which was 0.25 mg/ml. The applied nanocomposites using microdilution showed that CuO/Ag had approximately 98.8% and 98.7% efficiency on the respective Gram-positive and Gram-negative bacterial species, while ZnO/Ag achieved 91.7% and 89.3% efficiency, respectively, against the Gram-positive and Gram-negative bacterial species. This study presents a novel approach for relative analysis of the performance efficiency of transition metal based nanocomposites.